Pattern and progression of white-matter changes in a case of posterior cortical atrophy using diffusion tensor imaging. Issue 4 (16th March 2009) - Duning, T; Warnecke, T; Mohammadi, S; Lohmann, H; Schiffbauer, H; Kugel, H; Knecht, S; Ringelstein, E B; Deppe, M
Abstract : Background: The progression of white-matter changes in a case of posterior cortical atrophy (PCA) was examined over a period of 15 months using diffusion tensor imaging (DTI) and the association with neuropsychological variables was studied. Patient and methods: A PCA patient was observed over a period of 15 months. DTI and volumetric magnetic resonance imaging were obtained at visit 1 and 15 months later. Fractional anisotropy (FA) and volumetric changes were compared with findings in a typical case of Alzheimer disease (AD) and in 65 healthy volunteers, and the association of neuropsychological deficits with these changes was studied. Results: Reduction in FA was focused on the occipital lobe in the early stages of PCA. During the 15-month period, the FA values of the PCA patient tended to align with the FA ratios of the AD patient, with a more pronounced FA reduction in the parietal lobes, as opposed to a stable FA level in the occipital lobe. In addition to the DTI changes, clinical and neuropsychological symptoms deteriorated further. Brain volumes (grey matter, white matter and total normalised brain volume) of the PCA patient were substantially decreased compared with the control group, but loss of tissue volumes showed only marginal progression between visit 1 and 2. Conclusions: The findings suggest that PCA starts as distinct clinical syndrome but in its later course might turn into a final pathway shared with AD. DTI might be helpful in detecting changes in cerebral white matter during disease progression in PCA patients.